Performance of Teak Seedlings in Different Biodegradable Containers - Parida, S.; Kunhamu, T. K.; Jijeesh, C. M.; Anoop, E. V.; Sureshkumar, P. K. (Indian Forester, 2021)
A nursery trial was conducted to assess the performance of teak (Tectona grandis) seedlings in different biodegradable containers at College of Forestry, Kerala Agricultural University, Thrissur, Kerala, India in 2019-20. Nonwoven bag, bamboo split, coco pot, CNSL treated cardboard pot, mud pot and coir root trainer were used to grow teak seedlings. The teak seedlings of 0.5-month age were transplanted in such containers and their performance was evaluated after 2.5 months of transplanting. It was observed that considerable variability existed in seedling growth characters such as height, collar diameter, root: shoot ratio, root dry weight, shoot dry weight, total dry weight and seedling quality. Among all container types studied Nonwoven bag grown seedlings showed better growth performance followed by seedlings grown in bamboo split containers, while mud pot raised seedlings showed the lowest performance during all the stages of seedling growth.